2016
DOI: 10.1007/s00701-016-2873-6
|View full text |Cite
|
Sign up to set email alerts
|

Transposition of the paraclival carotid artery: a novel concept of self-retaining vascular retraction during endoscopic endonasal skull base surgery technical report

Abstract: Static repositioning of the ICA and other delicate neurovascular structures was effectively performed during endonasal, endoscopic cadaveric surgery of the skull base and has potential merits in live patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
(16 reference statements)
0
15
0
Order By: Relevance
“…The quadrangular space is considered as the "front door" for an endoscopic endonasal corridor accessing Meckel's cave. 11 Moreover, during an EEA to address lesions arising from both the medial petrous apex or the medial aspect of Meckel's cave, the paraclival ICA serves as a critical landmark. [16][17][18] In addition to the paraclival ICA, the development of an LPSB may also impact the exposure of Meckel's cave via an EEA corridor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quadrangular space is considered as the "front door" for an endoscopic endonasal corridor accessing Meckel's cave. 11 Moreover, during an EEA to address lesions arising from both the medial petrous apex or the medial aspect of Meckel's cave, the paraclival ICA serves as a critical landmark. [16][17][18] In addition to the paraclival ICA, the development of an LPSB may also impact the exposure of Meckel's cave via an EEA corridor.…”
Section: Discussionmentioning
confidence: 99%
“…9 The medial petrous apex can be accessed directly through the sphenoid sinus, although a lateral transposition of the paraclival ICA may be necessary to increase the exposure of the medial petrous apex. 10 Freeman et al 11 reported that an average of 4.75 mm of lateral transposition of the paraclival ICA could be achieved to increase the exposure of the petrous apex and the paramedial skull base. However, the existence of the lingual process of the sphenoid bone (LPSB), located at the lateral border of the paraclival ICA, may restrict the lateral displacement of the paraclival ICA.…”
mentioning
confidence: 99%
“…Freeman et al in their experimental work carried out lateralization of the ICA using a self-retaining vascular retractor and showed that the artery could potentially be displaced 4.75 mm laterally (the work was carried out only on cadaveric material), which could potentially turn out to be sufficient to complete the task; however, this manipulation is associated with certain risks, both from the sinonasal part and catastrophic bleeding from the ICA ( 13 ). It is necessary to be very careful in choosing this approach since this approach as a “monomethod” is not suitable for a strongly lateral or low location of the tumor.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…After completion of these steps, the ICA can be laterally mobilized approximately 4.5 mm to maximally expose the petrous apex. 7 The reaches of the endonasal endoscopic TMTP approach with and without ET resection and/or carotid mobilization were studied, as listed in Table 3. Moreover, there have been a number of cadaveric comparative analyses examining the differences between the TMTP approach and traditional transcranial alternatives.…”
Section: Approaches To the Petrous Apex And Petroclival Regionmentioning
confidence: 99%
“…We have previously shown that the combination of these maneuvers allows for an average carotid mobilization of 4.5 mm in the axial plane and exposes more of the superior portion of the petrous apex. 7 With static ICA mobilization, we were able to perform 4-handed, binostril surgery to maximize petrous apex resection. Whereas removal of the ET accesses the lower and middle portions of the petrous apex and petroclival region (Fig.…”
Section: Carotid Mobilizationmentioning
confidence: 99%